2015
DOI: 10.1016/j.rser.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy and growth: Evidence from heterogeneous panel of G7 countries using Granger causality

Abstract: In this paper we examine the causal relationship between renewable energy consumption and economic growth across the G7 countries, using annual data for the period of 1990 to 2011.By employing the causality methodology proposed by Emirmahmutoglu and Kose (2011), we investigate if there is a causal relationship between the variables. The advantage of this methodology is that it takes into account possible slope heterogeneity and cross-sectional dependency in a multivariate panel. The empirical results support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(77 citation statements)
references
References 32 publications
5
72
0
Order By: Relevance
“…Using the ARDL model, Sebri and Ben-Salha (2014) find the bidirectional causal relationship between the renewable energy and the economic growth in BRICS countries from 1971 to 2010. Using the heterogeneous panel Granger causality test, Chang et al (2015) also find the bidirectional causality between the renewable energy and the economic growth in the G7 countries from 1990 to 2011. Using the K-L model and the Toda-Yamamoto causality test procedure, Yildirim and Aslan (2012) investigate the validity of energy-growth nexus in 17 OECD countries.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Using the ARDL model, Sebri and Ben-Salha (2014) find the bidirectional causal relationship between the renewable energy and the economic growth in BRICS countries from 1971 to 2010. Using the heterogeneous panel Granger causality test, Chang et al (2015) also find the bidirectional causality between the renewable energy and the economic growth in the G7 countries from 1990 to 2011. Using the K-L model and the Toda-Yamamoto causality test procedure, Yildirim and Aslan (2012) investigate the validity of energy-growth nexus in 17 OECD countries.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Their empirical results indicated that renewable energy consumption plays a vital role in stimulating economic output. Chang et al (2015) examined the causal relationship between renewable energy consumption and economic growth across G-7 countries using annual data for the period of 1990-2011. Their results support the existence of a bi-directional causal relationship between economic growth and renewable energy for the overall panel.…”
Section: Panel Analysis On the Renewable Energy-economic Growth Nexusmentioning
confidence: 99%
“…Therefore, Delta  ) 5 test 5 In the  test approach, the first step is to compute the following modified version of Swamy's test as in . Chang, Rangan, Roula, Beatrice, Devon and Amy (2015). which is developed by for the first time, is applied to the variables.…”
Section: Testsmentioning
confidence: 99%